PENERAPAN PP NOMOR 46 TAHUN 2013 PADA PERHITUNGAN PPh TERHUTANG PT.AI TAHUN PAJAK 2013 - Handayani, Luh Indah; Novioari, Naniek (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
PP No.46 year2013 are one of government policy to increase tax revenues from mikro, small, and medium industry taxpayer. This research are exime how application PP No. 46 Year 2013 in tax reveneus payable calculation at PT.AI. Testing was done by descriptif comparatif analysis. This research are describe and compare the result of calculation tax reveneus payable with PP No. 46 Year 2013 than the result of calcution with general scheme tax reveneus regulation. The result are showed that tax revenues payable with PP No.46 Year 2013 are lower than  tax revenues payable with general scheme tax reveneus regulation. PP No.46 Year 2013 are give more simple and efisien calculation tax revenues payable to PT.AI.
Keywords: PP No. 46 Year 2013, Tax Revenues Payable